Comparison of Rotator Cuff Muscle Strength With and Without Scapular Dyskinesis in Adolescent Baseball Players - Il-young Yu; Tae-gyu Kim (Korean Research Society of Physical Therapy, 2024)
Background: Scapular dyskinesis (SD) is closely related to imbalance of the rotator cuff (RC) muscles. However, previous studies have only focused on isometric strength. To our knowl-edge, there has been no study examining potential differences in concentric and eccentric strength and functional strength ratio (FSR) of the RC muscles based on functional parameters related to throwing in with or without SD. Objects: This study aimed to determine whether there was a difference in the RC muscle strength and FSR between the dominant shoulder with SD and the non-dominant shoulder without SD in adolescent baseball players. Methods: Forty adolescent baseball players participated and classified types of SD based on movement patterns using the SD test by two examiners. The isokinetic concentric and ec-centric peak torque of the internal rotation (IR) and external rotation (ER) were measured and quantified as peak torque to body weight (PT/BW). Also, the FSR was obtained by calculating the strength ratios of eccentric IR to concentric ER (IRecc/ERcon) and eccentric ER to concentric IR (ERecc/IRcon), respectively. Results: There was a significant decrease in the IR and ER PT/BW in the dominant shoulder with SD compared to the non-dominant shoulder without SD (p < 0.05), regardless of con-traction types. However, no significant difference was observed in the FSR in both IRecc/ERcon and ERecc/IRcon ratios. Conclusion: The findings indicate that the isokinetic concentric and eccentric PT/BW of the IR and ER muscles were significantly lower in the dominant shoulder with SD than in the nonthrowing shoulder without SD. Therefore, when establishing a strategy for addressing RC muscle weakness in adolescent baseball players with SD, it is essential to consider an approach that accounts for scapular kinematic recovery.